Impact Of Instructional Aids On Students’ Academic Performance In Physics In Secondary Schools In Federal Capital Territory (FCT) Abuja, Nigeria - Adebayo, Odeniyi Olujinmi; Adigun, Saladin Quadri (European Scientific Journal, ESJ, 2018)
This research work investigated the extent of availability, application and impact of instructional aids on improving academic performance of physics students in Federal Capital Territory (FCT) secondary schools Abuja. The population of the study was limited to secondary schools in three Area councils of the FCT. The sampled schools used for the research had a total 3,150 students with teaching staff strength of 163. The study was carried out among the senior secondary SS2 and SS3 physics students and their teachers. Descriptive survey method was adopted for this study with 60 items on the questionnaire for students and 15 items for teachers. Six research questions were asked and analyzed using frequency counts and percentages. The data gathered were further analyzed and interpreted to arrive at findings which showed that the physics teachers in FCT secondary schools were using instructional aids, there was significant difference in academic performance of students taught with instructional aids; findings equally revealed that there were shortfalls in availability of some materials. Recommendations were suggested that government should formulate policy statement on availability, distribution, selection and maintenance of instructional aids in FCT secondary schools.